2019
DOI: 10.1289/ehp4913
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Household Air Pollution and Risk of Lung Cancer among Never-Smoking Women in Xuanwei and Fuyuan, China

Abstract: Background:Lung cancer rates among never-smoking women in Xuanwei and Fuyuan in China are among the highest in the world and have been attributed to the domestic use of smoky (bituminous) coal for heating and cooking. However, the key components of coal that drive lung cancer risk have not been identified.Objectives:We aimed to investigate the relationship between lifelong exposure to the constituents of smoky coal (and other fuel types) and lung cancer.Methods:Using a population-based case–control study of lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 46 publications
1
52
0
Order By: Relevance
“…Reducing residential solid fuel use will also lead to further public health benefits from reductions in household PM 2.5 exposure (Aunan et al., 2018; Chan et al., 2019; Kim et al., 2016; Li et al., 2019b; S. Li et al., 2019d; Vermeulen et al., 2019; K. Yu et al., 2018; Zhao et al., 2018). A reduction in residential solid fuel use may also reduce greenhouse gas emissions (Rive & Aunan, 2010; Smith & Haigler, 2008), depending on the replacement fuel (Qin et al., 2017; Yang & Jackson, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing residential solid fuel use will also lead to further public health benefits from reductions in household PM 2.5 exposure (Aunan et al., 2018; Chan et al., 2019; Kim et al., 2016; Li et al., 2019b; S. Li et al., 2019d; Vermeulen et al., 2019; K. Yu et al., 2018; Zhao et al., 2018). A reduction in residential solid fuel use may also reduce greenhouse gas emissions (Rive & Aunan, 2010; Smith & Haigler, 2008), depending on the replacement fuel (Qin et al., 2017; Yang & Jackson, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Reducing residential solid fuel use will also lead to further public health benefits from reductions in household PM 2.5 exposure (Aunan et al, 2018;Chan et al, 2019;Kim et al, 2016;Li et al, 2019b;S. Li et al, 2019d;Vermeulen et al, 2019;K. Yu et al, 2018;Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and mortality among rural residents are higher than those in urban residents [16]. For example, Xuanwei, Fuyuan [17,18] and Gejiu [19] in Yunnan province are regions with high incidence of lung cancer recognized by medical communities in both Chinese and other countries. And above reasons may further aggravate the public's biased perception of cancer, and even lead to the stigmatization and marginalization of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A study recently published in Environmental Health Perspectives identified specific constituents of smoke from the implicated coal that might be especially harmful-with potential significance far beyond rural China. 5 Bituminous coal is found everywhere in the world, says first author Roel Vermeulen, a professor of environmental epidemiology and exposome science at Utrecht University in the Netherlands. So why is the coal in this particular area so strongly associated with cancer risk?…”
mentioning
confidence: 99%